Intensification of climate-smart agriculture technology in semi-arid regions of India - Pal, Barun Deb; Kapoor, Shreya (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Technology adoption has been proven to be an efficient way to improve agricultural productivity as well as farmers’ income across the semi-arid regions of the globe. However, an upcoming method to improve food and livelihood security is through sustainable technology intensification. The study tries to assess the impact of climate-smart agriculture (CSA) technology intensification on farmers’ income using inverse probability weighted regression adjustment method. The results show a rise in average income for high intensified farmers in comparison to the low intensified farmers. The results also show a rise in income for CSA intensified farmers in comparison to the farmers adopting only improved technologies. Therefore, technology intensification of CSA technologies has been found to be an effective way in ensuring income security to the farmers.